OPTIMALISASI PEMASARAN DI ERA PANDEMI COVID-19 BAGI USAHA MIKRO KECIL DAN MENENGAH DI DESA BAWU - Rokhimah, Hafiza Meylia; Yuliana, Shofa Zulfriza; Naufal, Achmad; Lu'luatuwwafiroh, Lu'luatuwwafiroh; Ma'lufi, Muchammad Viqi; Anwar, Aan Zainul (Universitas Islam Nahdlatul Ulama Jepara, 2023)
The activity was a community service carried out in Bawu Village to a Micro, Small and Medium Enterprises (MSME) with the name BaimÂ¢s Cafe and Bubur & Rujak Mbok Siti. The spread of COVID-19 that hit Indonesia had a negative impact on micro-entrepreneurs in Indonesia, especially in Bawu Village. The implementation of Restrictions Towards Community Activities (PPKM) by both central and local governments significantly reduces consumer access to the micro business actors. The purpose of this community service is to increase the entrepreneurial knowledge and skills of business owners in selling through social networking. This service is carried out through mentoring activities including the creation and training of the use of social media in product sales, grab registration, relayout, redesign menu list, as well as monitoring and evaluation. The results obtained after mentoring showed an increase in consumer access to the assisted micro businesses, as indicated by the increase in orders and turnover of the assisted micro businesses. This activity is expected to be an example for other Micro, Small and Medium Enterprises business actors affected by the COVID-19 pandemic and become a solution to the existing problems.